Interaction of post-stroke voluntary effort and functional neuromuscular electrical stimulation - Makowski, Nathaniel (2013)
Functional Electrical Stimulation (FES) may be able to augment functional arm and hand movement after stroke. Post-stroke neuroprostheses that incorporate voluntary effort and FES to produce the desired movement need to consider how the forces generated by voluntary effort and FES combine together, even in the same muscle, in order to provide an appropriate level of stimulation to elicit the desired assistive force. The goal of this study was to determine if the force produced by voluntary effort and FES add together independently of effort, or if the increment in force is dependent on the level of voluntary effort. Isometric force matching tasks were performed under different combinations of voluntary effort and electrical stimulation. Participants reached a steady level of force and while attempting to maintain a constant effort level, FES was applied to augment the force. Results indicate that the increment in force produced by FES decreases as the level of initial voluntary effort increases. Potential mechanisms causing the change in force output are proposed, but the relative contribution of each mechanism is unknown.